Continuous Quality Improvement: A Perioperative Nursing Approach - Bruce-Barrett, Cindy; Espin, Sherry; Reichert, Catherine (Operating Room Nurses Association of Canada Journal, 1995)
This article describes in detail the steps taken in the Operating Room at the Toronto Hospital in implementing a Continuous Quality Management framework. Focusing on active participation, all levels of the O.R. staff worked through a process of identifying, developing, measuring and evaluating standards of practice. A step by step framework was followed in order to monitor current standards and develop new ones, thereby complying with the institution’s mandate of supporting Continuous Quality Improvement.